PROBLEM LEMBAGA PEMASYARAKATAN DI INDONESIA DAN REORIENTASI TUJUAN PEMIDANAAN - Ismail Rumadan (Jurnal Hukum dan Peradilan, 2013)
Many criminal problems that occurred in the prison showed that noble goal penitentiary establishment initiated by Sahardjo since its inception as a coaching institute, ethics and honor. That the person who lost had to give him stock diayomi live as good citizens and useful in society to be a difficult thing to achieve. This condition inspires us to re-review the (re-orientation) models that are used in a criminal prosecution of criminal law enforcement. Criminal law enforcement orientation semistinya not end at the prison in the form of criminal sanctions against the defendant, but the imposition of sanctions in the form of social sanction against the defendant with the crime scale reactive light need to be prioritized or preferably through a restorative justice approach. Keywords: Criminal Justice, the purpose of punishment, restorative justice.